GAMBARAN POLA MAKAN DAN STATUS GIZI SISWA MADRASAH DI WILAYAH PEDESAAN: STUDI KUANTITATIF PADA MI MIFTAHUL FALAH BANYUMANIS - Selvia, Dila; Islami, Islami; Septiani, Septiani (Darussalam Nutrition Journal, 2025)
Background: Dietary patterns and nutritional status play an important role in supporting the physical, cognitive, and academic development of elementary school students. Objective: This study aimed to describe the dietary patterns and nutritional status of grade IV–VI students at MI Miftahul Falah, Banyumanis Village, Donorojo Subdistrict, Jepara Regency. Methods: This was a descriptive quantitative study. The sample consisted of 81 students drawn using a total sampling technique. Dietary pattern data were collected using the SQ-FFQ, and nutritional status was measured using Z-Score. Data were analyzed using frequency tests. Results: Most students (97.5%) consumed main meals at least three times per day. Adequate carbohydrate intake was found in 98.8% of students, adequate animal protein in 97.5%, while plant-based protein intake was still low in 9.9%. Vegetable consumption was relatively good, with 60.5% consuming ≥3 servings per day, and fruit intake was adequate in 67.9% of students. However, unhealthy dietary habits were still common: 49.4% frequently consumed sweet foods 4–6 times per week, 45.7% consumed sweet drinks, and 45.7% consumed fried foods, snacks, or processed foods, with 17.3% consuming them very frequently (>6 times per week). Nutritional status showed that 81.5% of students were normal, 2.5% undernourished, 8.6% overweight, and 7.4% obese. Overall, around 16% of students were overweight. Conclusion: Students’ dietary patterns and nutritional status were relatively good. Nutrition education and continuous monitoring are required to increase awareness of healthy food consumption and to prevent nutritional imbalances.